Numerical Study on Flow-Induced Noise of Deflector Jet Servo Valve Based on LES/Lighthill Hybrid Method. (22nd March 2022) - Ren, Yukai; Yan, Hao; Cai, Cunkun
Abstract : The flow-induced noise occurring in the prestage of the deflector jet servo valve (DJV) significantly affects the performance of DJV, which is a critical issue for electrohydraulic servo valves. To capture the root causes of flow-induced noise, DJV is numerically studied using computational aeroacoustics (CAA) methods in this paper. The acoustic field is investigated with Lighthill's acoustic analogy based on the pulsation data from a large eddy simulation (LES). The flow-induced noise generation mechanism in DJV is revealed by analyzing the sound pressure level and vorticity distribution at different moments. Moreover, a kind of oscillation cavity model based on the Helmholtz oscillator is built, which reveals that the flow-induced noise is caused by self-excited oscillation and vortex. In addition, the result shows that continuous broadband dipole noise with medium- and high-frequency components of 1100 Hz and 2501 Hz dominates the DJV flow field. In order to avoid unexpected resonance, the natural frequency of the prestage should not coincide with the frequency of the flow oscillation frequency. Thus, this work can benefit the design and optimization of the prestage structure.